Three-dimensional Biopharmaceutics and Clinical Considerations of Drugs for Safety and Efficacy: A Review Study - Sunday O. Awofisayo; Akwaowoh E. Akpabio; Emmanuel O. Olorunsola; Matthew I. Arhewoh (Pharmaceutical and Biomedical Research)
Background: Several drugs today are described with their molecular structures showcasing symmetrical, dissymmetrical, or asymmetrical configurations. Some drugs showing chirality are racemic or pure enantiomeric forms for clinical practice. Objectives: This review outlines the mechanistic protocols of kinetic disposition of enantiomers alongside their discriminatory reactions with receptors based on chemical, structural, and conformational orientations that form the objective of this review. Methods: Articles published from 2001 to 2023 were sorted and reviewed manually from Google Scholar and other scientific databases (e.g. PubMed, Medline, Web of Science, Embase, and Scopus) using words and phrases such as “enantiomer”, “racemates”, “biopharmaceutics”, “enantioselectivity”, “three-dimensional drugs”, and “molecular inversion”. Results: There is evidence that chirality exists in biological systems as macromolecules (e.g. lipids, amino acids, carbohydrates, phospholipids, nucleosides, glycoproteins, glycolipids, etc.) in the human body’s layout. Stereochemistry is gaining greater attention in biopharmaceutics and pharmacotherapy as clinicians are challenged to make informed decisions regarding using either single-enantiomer or racemic drugs. The stereocenter’s vivid configurational focus and three-dimensional reactivity are well amplified by the concept of enantioselectivity exhibiting pharmacokinetic and pharmacodynamic implications. Some clinical-toxicological effects have been linked to the other enantiomer in pharmacotherapy. Using racemates continues despite the enantiomeric pharmacokinetic and pharmacodynamic differences of the isomers. Conclusion: The dramatic transformations of enantiomers alongside their in vitro and in vivo behaviors (i.e. molecular inversion and interconvertibility) are intriguing. The additional protocols of scientific resolution and purification of racemates in drug development may be the spark of more refined three-dimensional biopharmaceutics.